PENGARUH ABU VULKANIK PADA PERTUMBUHAN, LUAS SERANGAN DAN INTENSITAS SERANGAN KARAT TUMOR PADA SEMAI SENGON - Siti Husna Nurrohmah; Agus Wahyudi; Liliana Baskorowati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2014)
The study aimed to examine the effect of volcanic ash on growth, disease incidence and severity of gall rust on sengon seedlings. Treaments were used compound af volcanic ash and planting medium with the comparison of 0:4 (M1), 1:3 (M2), 1:1 (M3), 3:1 (M4) and 4:0 (M5). Growth parameters including height, number of leaves, and the level of chlorophyll were measured. Artificial inoculation using fresh spore of Uromycladium tepperianum were applied 3 times: at the first, fourth and seven days after the second leaves of seedlings emerged, then the gall rust disease symptom were scored weekly for a month. The results showed that seedlings exhibited treatment M1 and M2 more optimal growth than the others. However, sengon with higher concentration volcanic ash performed the slowest growth compared to other treatments. Disease incidence and severity were ranged of 0-80% and 0-24%. Seedling sengon with treatment M2, M3 and M5 emerged the symptoms of gall rust however, seedlings with treatments of M1 and M4 did not show the symptomps.